PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Dzikra Oktavia; Nugi Mohammad Nugraha (Jurnal Computech & Bisnis (e-Journal), 2020)
This study aims to determine the effect of invesment decisions, funding decisions, and dividend policy on the value of companies Miscellaneous Industry listed on the IDX period 2014 to 2018. The dependent variables in this study is values of companies while the independent variable in this study are invesment decisions, funding decisions, and dividend policy. The data used in this study are secondary data obtained from the official website of Indonesia Stock Exchange. Total of sample is 6 companies selected using purposive sampling method. Data analysis used in this research is panel data regression analysis with multiple linier regression method. The results of this study indicate that jointly invesment decisions, funding decisions, and dividend policy have a significant effect on the value of companies in the miscellaneous industry listed on the IDX period 2014-2018. Partial research results that invesment decisions and funding decisions have a significant effect on corporate value.Keywords : Invesment Decision, Funding Decision, Dividend Policy, Corporate ValueDOI : http://doi.org/10.5281/zenodo.3928952